Social and economic inequalities in the circumpolar Arctic - Duhaime, Gérard; Caron, Andrée; Lévesque, Sébastien; Lemelin, André; Mäenpää, Ilmo; Nigai, Olga; Véronique Robich; Robichaud, Véronique (Statistics Norway, 2024)
In our previous comparative study for 2006, in The Economy of the North 2008, we showed that there are important differences in social and economic conditions across the circumpolar Arctic. We collected widely used indicators of demography, health, education and economic situation. The results suggested the existence of distinct patterns that characterized the socio-economic differences between the main geopolitical groups of Arctic regions, in North America, the Nordic countries, and the Russian Federation.The study reported here updates and extends the comparative study and explores some aspects of inequality in economic and social conditions across the circumpolar Arctic. We extended the methodology we developed for The Economy of the North 2008, in order to compare the situations in 2012 and 2006. Comparing the indicators allowed us to verify whether the models we previously identified for 2006 are still relevant in 2012. The results also allowed us to see if the relative ranking of regions and sub-regions is still valid. 0